АНАЛІЗ ОСОБЛИВОСТЕЙ ВИКОРИСТАННЯ ДАНИХ ВІД ПРИСТРОЇВ ВИМІРЮВАННЯ ФОРМИ СИГНАЛІВ СТАНУ ЕНЕРГЕТИЧНОЇ МЕРЕЖІ - Войтов, Д.В. (Інститут електродинаміки Національної академії наук України, 2026)
In this work the development of energy networks’ monitoring to obtain more detailed information about their main signals is examined. The focus of the article is a new type of current and voltage sensors – WMUs (waveform measuring units) and their capabilities compared to similar devices. A number of scientific and applied works on the topic of application of information received from WMUs are analyzed. Main methods for data usage obtained from WMUs to ensure greater awareness of the energy quality in the system are briefly investigated. Particular attention is paid to the application of Lissajous curves built on signals received from WMUs, both in theoretical and practical areas. The positive and negative features when using WMUs and devices used to solve similar problems in Ukraine are outlined (PMU – phasor measurement unit and PQA – power quality analyzer). Ref. 11, fig. 3, table.